Control of information originating from Aboriginal communities: Legal and ethical contexts - Bell, Catherine; Shier, Caeleigh (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2011)
Access to and control over data and products of research originating from, or about, Aboriginal peoples in Canada arises in multiple legal, ethical, and political contexts. This article addresses three areas frequently implicated in Canada: intellectual property, access to information, and tribunal law and policy. A review of each area demonstrates that effective responses to concerns of Aboriginal peoples in Canada require examination of a wide range of laws implicating Inuit, First Nation, and Métis intangible and tangible cultural heritage. It also underscores the present importance of contracted confidentiality and negotiated ethical and policy frameworks to secure more meaningful control over information.